Collaboration on the Development of Kemaro Island as a Leading Tourist Destination for the City of Palembang - Darmanto, Darmanto; Istianda, Meita; Wahyudi, Heri (Universitas Ibn Khaldun Bogor, 2024)
The Palembang City government's agenda to develop Kemaro Island as a leading tourist destination has not received a positive response from the community, especially those involved in the program. This research aims to explain local government policy, especially from the perspective of Palembang city government policy in developing Kemaro Island, Palembang City as a leading tourist destination. The method used is a comprehensive and systematic qualitative review of the factual problems that occurred as well as the various efforts that have been made by various parties related to the existence of Kemaro Island. The findings obtained from the results of this research are the need for a systematic approach in making policies for the development of Kemaro Island through collaboration with various stakeholders. The importance of collaboration is emphasized and recommendations are offered to improve collaboration. This article provides lessons on how to manage the development of superior tourist destinations through understanding the problems that occur as well as aspects of collaboration between various stakeholders effectively to produce effective policies in the development of superior tourist destinations. The author suggests the need for community participation through the concept of collaboration to produce effective policies for developing superior tourist destinations.